Efeito das características infantis sobre a cooperação: análise ontogenética por uma perspectiva evolucionista - Leitão, Monique Bezerra Paz (2015)
Babies and young children are often considered graceful and evoke much affection. The tendency to perceive them in a positive manner and the propensity to care for them are assigned to physical and behavioral traits typical of an infant. In humans, facial features such as large eyes relative to the face and rounded head are important stimuli. Some theorists argue that the human cooperation tendency is rooted in mechanisms that have evolved to care for offspring, however few studies investigated the relationship between children's traits, perceptions of cuteness and cooperation. In this work it was developed four publications. The first investigated the influence of age range and sex in the expression of cooperative and competitive behaviors and perception of childishness on the part of older individuals by interacting with young children. Took part of the study 244 subjects (120 females) who interacted in dyads during tic-tac-toe matches. Dyads tested were: Child 4-5 x Child 8-9 years old; Child 4-5 x Adolescent 14-16 years old; Child 4-5 x Adult 25-35 years old. Children aged 8-9 years expressed more competitive behavior, especially dyads of opposite sex, and adults expressed more help. Adolescents and adults tended to evaluate the young child as cuter, more beautiful and more naïve. The higher the cuteness evaluation, the lower competition by children aged 8-9 years and adults. The second publication describes the construction and validation of the Child Neutral Expression Picture Set - CNEPS, a database face made up of images of 131 children between 4-5 years old with neutral facial expression. After capturing, editing and standardizing, the images were evaluated by experts, generally being considered with neutral expression. The third publication aimed to measure and correlate the facial infant traits of children's image with positive perceptions, competitive and cooperative behaviors in the game toward these children by subjects of different ages. The subjects and method were the same used in the first publication, adding the traits' measurement. The study is innovative by showing that the perception and frequency of competition and helping vary according to the intensity of certain baby schema traits in all age groups. Among children 8-9 years old the traits correlated to the perception of cuteness, among the adolescents they were related to both the positive perception and competition inhibition. In adults, the traits correlated with more help. The fourth publication is a technical note describing datasets of facial images of children and adults available for scientific research. In summary, this thesis showed that across the lifespan, individuals tend to act more cooperatively with small children, evaluate them more positively and that specific infant traits influence the decreased competitiveness and increased cooperation. It is understood that several cognitive and behavioral adaptations were favored during human evolution to promote care and protection of immature individuals, especially considering the high level of dependency and long-term care required by our infants.